STRATEGI HEDGING DAN INDIKATOR BILL WILLIAMS DALAM UPAYA MEMAKSIMUMKAN PROFIT INVESTASI FOREX - I Gusti Ngurah Putra Vasudeva (Universitas Pendidikan Nasional, 2015)
Forexis an alternative type of highly liquid investments. The liquidity level and priceacceleration that occurs in the forex could close the transaction quickly and profit levelexceeded the average trade in general. However, rapid price movements in the forex also causea high degree of volatility that the forex became a very risky investment so it is difficult tomaximize profit. Researchers use hedging techniques to drive price movement suddenly turnedaround and indicators of Bill Williams to analyze price movements that would happen tooccurin the future.This research used qualitative destuctive analysis to see that the hedging technique and BillWilliam Indicator could maximize forex invesment profit. The study was conducted for fivemonths starting from the date of July 1, 2014 until November 30,2014, through Octa FXservice.Researcher got a margin call when run hedging technique in the first time. Researcher modifiedhedging techniques after knowing its weakness. And finally the problem of hedging techniqueswas resolved. Collaboration between hedging techniques and Bill Williams indicators couldmaximize profits in forex investment.Keywords : hedging, Bill Williams indicator, investment, forex.